New cytogenetic data on Coreoidea (Hemiptera: Heteroptera) with special reference to Coreidae - Yang, Hailin; Li, Hu; Dai, Xun; Chang, Jian; Cai, Wanzhi (Zootaxa, 2012)
Some cytogenetic aspects of six Chinese species of Coreoidea were studied. The material included five species from the familyCoreidae: Hydarella orientalis (Distant), Homoeocerus bannaensis Hsiao, Cletus graminis Hsiao & Cheng, Paradasynus lon-girostris Hsiao, Acanthocoris scaber (Linnaeus), and one species from the family Stenocephalidae: Stenocephalus femoralisReuter. All species show holokinetic chromosomes, post-reductional meiotic division of XO sex chromosomes, a pre-reduc-tional type of meiosis for autosomes and m-chromosomes, intersticial chiasmata in most autosomes, and one chiasma per biva-lent in male meiosis. In the species studied, the diploid chromosome number ranged from 13 to 21. It was 13 in S. femoralis (10+ 2m + XO), 15 in Hy. orientalis (12 + 2m + XO), 17 in Ho. bannaensis (14 + 2m + XO) and C. graminis (14 + 2m + XO), 19in P. longirostris (16 + 2m + XO), and 21 in A. scaber (18 + 2m + XO). Hy. orientalis represents the first cytogenetically stud-ied species in subfamily Hydarinae. The phylogenetic relationships among Coreoidea are briefly discussed from a cytogenetic point of view.